PENGARUH COMPETITOR ACCOUNTING SEBAGAI STRATEGIC MANAGEMENT ACCOUNTING TECHNIQUES TERHADAP COMPETITIVE ADVANTAGE DAN ORGANIZATION PERFORMANCE - Alan, Hartanto (Business Accounting Review, 2015)
The purpose of this study was to know the affect of Competitor Accounting as a Strategic Management Accounting Techniques toward Competitive Advantage and Organization Performance on manufacturing companies in Surabaya and Sidoarjo. In this study primary data was used by using questionnaire distributed to manufacturing companies in Surabaya and Sidoarjo. This study used path modeling analysis technique with PLS tools. From the examination showed that there were positive and significant affect of Competitor Accounting as a Strategic Management Accounting Techniques towards Competitive Advantage, positive and significant affect of Competitor Accounting as a Strategic Management Accounting Techniques towards Organization Performance, and also positive and significant affect of Competitive Advantage towards Organization Performance on manufacturing companies in Surabaya and Sidoarjo.